2017
DOI: 10.1308/rcsann.2016.0282
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgical experience on the amount of radiation exposure from fluoroscopy during dynamic hip screw fixation

Abstract: INTRODUCTION Dynamic hip screw (DHS) fixation for proximal femur fractures is one of the most common procedures in trauma that requires the use of fluoroscopy. Emphasis is often placed on producing the 'perfect picture', which may lead to excessive use of fluoroscopy, without added patient benefit. This study, the largest of its kind, aimed to determine the effect of surgical experience on the amount of radiation exposure from fluoroscopy during DHS fixation. METHODS All hospital admissions for extracapsular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…conducted their study in the UK, and thus their grading was based on the traditional UK specialization tiers of consultants, senior registrars and junior registrars. 30 Quah, 31 Madan, 7 Bahari 20 and Giannoudis, 26 followed as similar tier system.…”
Section: Grading Of Surgeon Experiencementioning
confidence: 95%
See 1 more Smart Citation
“…conducted their study in the UK, and thus their grading was based on the traditional UK specialization tiers of consultants, senior registrars and junior registrars. 30 Quah, 31 Madan, 7 Bahari 20 and Giannoudis, 26 followed as similar tier system.…”
Section: Grading Of Surgeon Experiencementioning
confidence: 95%
“…With the exception of four studies, 24,27,31,34 all remaining studies reported Total Fluoroscopy time(TFT)/Screening time. Majority of the studies found a longer TFT when surgeries were being performed by a junior inexperienced resident/trainee.…”
Section: Total Fluoroscopy Time/screening Timementioning
confidence: 99%
“…On the contrary, Quah et al [ 14 ] found that the registrar cohort as a whole (ST3-ST8), cumulatively used a higher dosage of ionising radiation compared to the consultant cohort for an extended series of 1203 patients. It is notable that this study again compared two extremes of surgical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Al parecer, existe controversia respecto a la dosis necesaria para el desarrollo de cataratas, pero si se consideraba que existía un efecto determinista a partir de 5 a 8 Gy, actualmente se ha bajado el nivel a 0,5 Gy. Finalmente, e importante para aquellos que nos dedicamos a la docencia, la cantidad de radiación que recibimos es inversamente proporcional a la experiencia quirúrgica y a la complejidad de la cirugía a tratar (7) . Este es un motivo más para enfrentar al residente de forma progresiva a problemas cada vez más complejos.…”
Section: Las Radiaciones Ionizantesunclassified